Mechanical Properties and Microstructural Behavior of Uniaxial Tensile-Loaded Anisotropic Magnetorheological Elastomer - Siti Fatimah Mohd Shahar; Saiful Amri Mazlan; Norhasnidawani Johari; Mohd Aidy Faizal Johari; Siti Aishah Abdul Aziz; Muntaz Hana Ahmad Khairi; Nur Azmah Nordin; Norhiwani Mohd Hapipi (Actuators, 2022)
Magnetorheological elastomers (MREs) are well-known for their ability to self-adjust their mechanical properties in response to magnetic field influence. This ability, however, diminishes under high-strain conditions, a phenomenon known as the stress-softening effect. Similar phenomena have been observed in other filled elastomers; hence, the current study demonstrates the role of fillers in reducing the effect and thus maintaining performance. Anisotropic, silicone-based MREs with various carbonyl iron particle (CIP) concentrations were prepared and subjected to uniaxial tensile load to evaluate high-strain conditions with and without magnetic influence. The current study demonstrated that non-linear stress–strain behavior was observed in all types of samples, which supported the experimental findings. CIP concentration has a significant impact on the stress–strain behavior of MREs, with about 350% increased elastic modulus with increasing CIP content. Microstructural observations using field emission scanning electron microscopy (FESEM) yielded novel micro-mechanisms of the high-strain failure process of MREs. The magnetic force applied during tension loading was important in the behavior and characteristics of the MRE failure mechanism, and the discovery of microcracks and microplasticity, which was never reported in the MRE quasi-static tensile, received special attention in this study. The relationships between these microstructural phenomena, magnetic influence, and MRE mechanical properties were defined and discussed thoroughly. Overall, the process of microcracks and microplasticity in the MRE under tensile mode was primarily formed in the matrix, and the formation varies with CIP concentrations.